Qualitative Process Evaluation of an Agricultural Livelihood Project in Bangladesh: Multi-Sectoral Nutrition Programming Through Implementation Science. (7th June 2021) - Joarder, Taufique; Evens, Emily; Hoke, Theresa; Crum, Jennifer; Seal, Ayan; Hasib, Enam; Rizwan, Ashfique; Weissman, Amy
Abstract: Objectives: We conducted a process evaluation to examine the perceptions of program implementers, community leaders, and beneficiaries to assess the intervention's acceptability and to document how multisectoral agricultural livelihood interventions were implemented. Methods: Interventions were implemented from March 2019 to March 2020 in 30 unions of three Bangladeshi districts. Delivered by community partners, interventions aimed to improve health and nutrition service utilization, social and behavior change regarding infant and young child feeding (IYCF), and homestead food production (through community farmers or private sector agro-input retailers) among poor mothers of under-two children. Leveraging the RE-AIM framework, we evaluated implementation through in-depth interviews with service providers ( n = 13), focus group discussions with beneficiaries (8 sessions), and process documentation (12 events). Results: Most service providers, community leaders, and beneficiaries expressed satisfaction with interventions and a desire to continue participation. Beneficiaries especially appreciated the health and nutrition education provided through different formats, including mothers' group meetings, voice messages, home visits, counseling at health facilities, and education on food production by community farmers or retailers. Additionally, beneficiaries described increased health knowledge and highly valued material benefits offered through vegetable seeds and poultry rearing inputs. Beneficiaries appreciated retailers' support to grow vegetables and raise chickens and awareness efforts on the importance of good nutrition and IYCF practices. However, findings suggested community farmers offered more interpersonal support than retailers. Service providers noted the importance of sustained community engagement. Conclusions: Findings suggest that tested interventions combining food production with health and nutrition education are a viable, acceptable approach to promoting improved IYCF practices. Existing community-based organizations can reach vulnerable households with multisectoral nutrition approaches. Funding Sources: United States Agency for International Development (USAID).